Turismo e meio ambiente: aspectos ambientais na Serra do Tepequém – Amajarí/RR - Tomé, Djenane de Lima (2017)
Tourism is a complex phenomenon and it is seen as an alternative to foster development. Regardless of the type of tourism, it generates impacts, which can be social, economic and environmental. However, if tourism is carried out in an organized and planned way, it can promote more positive than negative impacts. In Roraima, tourism is still little explored, but there are attractions that have been gaining prominence at a national level, such as Serra do Tepequém, for its exuberant landscapes and beauty, besides a pleasant weather among other characteristics that make it unique. Serra do Tepequém is located in the north of the state of Roraima, more specifically in the Region of Amajarí, 213 km from the capital Boa Vista. The mining exploitation has become a historical landmark, in the 90's, when the first village was formed, where it is now known as Vila Tepequém or Vila do Paiva. Nowadays the mountain is one of the most visited tourist spots. The flow of visitors has increased and consequently so have the impacts generated. The objective of this work is to identify the environmental impacts at Serra do Tepequém - RR, due to the use of natural resources by the tourist activity, according to the local actors´ view. The nature of this research is both qualitative and quantitative. A questionnaire was used to collect data and local actors linked to tourism were interviewed, in addition to participant observation. The garbage left by visitors in a place was admitted as an environmental problem. The community´s increasing income and employment was identified as a positive impact, in the view of the actors. It has been found that nature, weather and peacefulness are the main aspects that determine the attractiveness of the place. Therefore, those aspects should be considered for tourism planning in the region, since government representatives still do not have enough interest and do not invest to make this activity more efficient for the development of the region. In this context, as a result of the problems detected, some guidelines were suggested in order to contribute to a potential planning regarding those questions.